Chemical kinetics and reaction mechanisms - James H Espenson (New York McGraw Hill, Inc., 1995)
Reaction and reaction rates; Reaction with simple kinetic form; Reaction in solution; Deduction of reaction mechanisms.
Keywords: Chemic dynamics, static and equilibrium